Versão COPPE do TWM para simulação em bacias hidrográficas com solos residuais - Magalhães, Paulo Canedo de (1974)
This report is concerned about a parametric model for hydrological simulation of hydrografic basins wih residual soils, based on SWM IV e TWM. The model makes total discharges simulation for any interval of time so as its components and evapotranspiration, starting from rainfall data and soil physical characteristics. Programmed to be used by 150k bytes memory computers, the model works a whole hydrological year in about 3 minutes.